2020
DOI: 10.1007/s10067-020-05371-2
|View full text |Cite
|
Sign up to set email alerts
|

Things left unsaid: important topics that are not discussed between patients with systemic sclerosis, their carers and their healthcare professionals—a discourse analysis

Abstract: Introduction Systemic sclerosis (SSc) is a rare condition that can be complicated by interstitial lung fibrosis (SSc-ILD)—a major cause of mortality. This study explored information and communication needs of patients with SSc-ILD and their carers to understand what they are and whether they are met. Methods Qualitative research was performed, including in-depth individual interviews and observed conversations between pairs of patients, physicians and nurses, and between patients and physicians discussing ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…However, in this study both patients and HCPs indicated that patients have limited understanding of the disease, particularly at the time of diagnosis, when they are confused. It is well-known that during consultations, physicians often revert to medical terminology when the issue becomes complex, while patients use medical terminology without sufficient understanding of the terms [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study both patients and HCPs indicated that patients have limited understanding of the disease, particularly at the time of diagnosis, when they are confused. It is well-known that during consultations, physicians often revert to medical terminology when the issue becomes complex, while patients use medical terminology without sufficient understanding of the terms [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“… 6 Moreover, the presence of dedicated nurses helps patients to feel free to ask questions about their condition. 7
Figure 1 Different clinical domains of systemic sclerosis and a suggested multidisciplinary approach.
…”
Section: Introductionmentioning
confidence: 99%
“…It can be difficult for patients to develop a clear understanding of the diagnosis, prognosis, and treatment options. 10,11 However, if patients are not educated about the disease and its course, key patient priorities may not be addressed. Communication challenges between patients and physicians can lead to suboptimal disease management.…”
Section: Introductionmentioning
confidence: 99%
“…The need to improve health care professionals’ communications with patients and to involve them in decision-making is increasingly being recognized. 10,11,53 Currently, there are no curative therapies for SSc-ILD and it is important that patients understand this. Nevertheless, as mentioned earlier, there is evidence to support the use of the recently FDA-approved agent nintedanib, 17 and the recommended immunosuppressants, cyclophosphamide, and mycophenolate mofetil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation